Mediasi Kepuasan Kerja Terhadap Kinerja Karyawan Pada Usaha Jasa Keuangan - Tjahyanti, Setia; Fatikhasari, Zalfa Ardanti; Suryawan, Ian Nurpatria (Forum Kerjasama Pendidikan Tinggi, 2025)
The purpose of this study is to examine the effect of work-family conflict, work stress on employee performance through job satisfaction at PT X. The population used in this study were 83 employees of PT X and the sample used was 66 employees with a purposive sampling technique. The data of this study were collected using a questionnaire with a Likert scale measurement and the analysis method used in this study was variance-based structural equation modeling with partial least square (PLS-SEM). The results of this study indicate that work-family conflict has an influence on job satisfaction, work stress has an influence on job satisfaction, work-family conflict has an influence on employee performance, work stress has an influence on employee performance, job satisfaction has an influence on employee performance, work-family conflict has an influence on employee performance through job satisfaction, work stress has an influence on employee performance through job satisfaction.